Impact of Recombined Milk Systems on Gastrointestinal Fate of Curcumin Nanoemulsion - Qazi, Haroon Jamshaid; Ye, Aiqian; Acevedo-Fani, Alejandra; Singh, Harjinder (Frontiers in Nutrition, 2022)
Milk powder is an important ingredient in various foods and paediatric formulations. The textural and digestion properties of the formulations depend on the preheat treatment of the milk powder during manufacture. Thus, it is interesting to know how these modifications can influence on the release of fortified bioactive compounds during digestion with a milk matrix. In this study, a curcumin nanoemulsion was incorporated into milks reconstituted from low-heat, medium-heat and high-heat skim milk powders and the milks were subjected to semi dynamic in vitro digestion. All the recombined milk systems formed a curd under gastric conditions, which reduced the gastric emptying of protein and curcumin-loaded oil droplets. Because of the formation of heat-induced casein/whey protein complexes, the open fragmented curd formed by the high-heat-treated reconstituted powder resulted in higher protein and oil droplet emptying to the intestine and higher curcumin bioaccessibility. This study provides useful information for how protein ingredients can govern the fate of added health-promoting compounds during digestion.